The International Politics of Nuclear Waste - Blowers, Andrew. author. aut Link
XXII, 362 p.
Keywords: Looking at the politics of nuclear waste, this book examines the subject from an international standpoint. Other works by the author Andrew Blowers include "The Limits of Power" and "Something in the Air", and he has been co-editor on books such as "Nuclear Power in Crisis".